Culture and psychological development - Empson, Janet M. (Janet Margaret), 1947- (Basingstoke [England] : Palgrave MacMillan, 2010)
'From infancy through to school age and beyond, most children are in constant contact with an array of social influences. Home life, education, community and the media all play some part in a child's development. In this book, the authors discuss the ways in which such diverse cultural settings affect behaviour and how children are shaped by the world around them. They examine development from both a cultural and cross-cultural perspective, drawing on case studies, to illuminate theoretical insights.'--BOOK JACKET.
Includes bibliographical references and indexes.
Keywords: Culture; Ethnopsychology